To the Question About the Fauna of Spiders (Aranei, Arachnida, Arthropoda) of Three Families of Spiders - Jumping Spiders (Salticidae), Pit Spiders (Araneidae) and Crab Spiders (Thomisidae) of the Reserve Kozakova Dolyna - Venhryniuk, Ihor; Артур (Journal of Vasyl Stefanyk Precarpathian National University. Biology, 2023)
For the first time, a study of the spider fauna (Aranei, Arachnida, Arthropoda) of the "Kozakova Dolyna" reserve, which is distinguished by various floral complexes and a peculiar geological structure: these are karst gypsum mountains formed in the Torton epoch of the Neogene period, was conducted. Gypsum mountains of the reserve have numerous caves, rocks, karst craters, which contributes to the diversity of the spider fauna. The spider fauna of the Ukrainian Carpathians and Carpathians (in contrast to many other regions of Ukraine) still remains extremely insufficiently and fragmentarily researched and requires further research. The fauna of spiders of three families was studied: Jumping spiders (Salticidae), Orb-weaver spiders (Araneidae) and Crab spiders (Thomisidae) of three families, which differ in the diversity of species both in the world fauna and in the fauna of Ukraine. The studied collections were collected over a long period of time - from 2002 to 2023 inclusive. Material collection and species identification were carried out in a standard manner. The collected material was stored in 70% ethanol. As a result of research conducted on the territory of the "Kozakova Dolyna" nature reserve and adjacent territories, 40 species of spiders of the three families mentioned above were found. An analysis of the biotope distribution of the detected species was carried out, the faunal affinity of species complexes of spiders was investigated according to the criteria of faunal affinity of Jacquard (S) and Sorensen (KS), and an areological analysis of the detected species was carried out. It was established that the beech forest edge ecotone is the richest in spider species (39 identified species). The ecosystem of the forest floor of the beech forest turned out to be the poorest in terms of species complexes of spiders of the three studied families. A cluster statistical analysis was carried out on the basis of faunal affinity data. The closest species complexes of spiders of the three studied families were the forest edge ecotone of beech forests and steppe areas in the vicinity of the "Kozakova Valley" reserve (S = 81.15; Ks = 0.899). The ecosystems of the steppe areas and the forest floor of the beech forest turned out to be the least related in terms of spider fauna (S = 6.25; Ks = 0.118). The most species of spiders with a Holarctic range (10) and a transpalearctic range (9) were found. 5 species have been identified with a European range. No new species for the fauna of Ukraine were found. No endemic species were found.